Analysis of Need for Development of STEAM-SDGS Based Science and Science Learning Tools on Energy Material and Its Changes to Increase Creativity and Science Process Skills of Vocational School Students - Hindradi Hindradi; Fenny Roshayanti; Nur Khoiri; Siti Fatonah (UIN Fatmawati Sukarno Bengkulu, 2025)
The Industrial Revolution 4.0 requires human resources in the world of work to be of good quality and competent in their field of competence. Therefore, educators must be able to innovate in science learning. 21st-century learning must be relevant to developments in science and technology. Students' potential that can be developed in facing the 21st century includes creativity and science process skills in learning. School science learning often tends to be boring and does not develop creativity and science process skills. The development of STEAM-SDGS-based learning tools with the Project Based Learning model is needed to meet the demands of education in the 4.0 era. This research aims to analyze the need to develop STEAM-SDGS-based learning tools. This type of research is survey research using quantitative descriptive research methods. The population in this study were all class X students at SMKS Bhakti Mulia Wonogiri, with a research sample of 62 students. The research was conducted in May 2024. The data collection technique used a questionnaire with a modified Likert scale with four answer choices: strongly agree, agree, disagree, and strongly disagree. The research results showed that the statements submitted to respondents obtained a percentage of 11% -40%, which fell into the categories of strongly disagree and disagree. From these results, science and science learning tools are based on energy and its changes to increase vocational school students' creativity and science process skills.